Combined lysine and cobalt supplementation improves semi-thermophilic anaerobic digestion performance with enhanced Methanosarcina-associated methylotrophic potential - Changxun Zhao; Jiefei Mo; Zhiru Peng; Jia Cheng; Ouru Zhan; Yabin Gong; Yintian Mao; Yong Qin; Weixiang Wu (Bioresource Technology, 2027)

Quality formation mechanism of shiitake mushrooms during multiphase microwave drying (MMD) - Zhenbin Liu; Jia Luo; Jiayi Zhang; Rui Weng; Wenchao Liu; Hongbo Li; Huan Cheng; Dong Wang; Hengchao E; Lu Tian; Haizhen Mo; Liangbin Hu (Food Control, 2026)

Integrating lipid metabolomics and epidemiology: A mediation analysis of blood lipids between per- and polyfluoroalkyl substances (PFAS) and renal impairment - Dandan Xu; Zhe Mo; Jie Xiang; Ping Cheng; Peiwei Xu; Yuan Chen; Xinhan Zhang; Qing Liu; Zhijian Chen (Environmental Pollution, 2026)

Mn‑doped lignin‑derived carbon aerogels for room‑temperature formaldehyde degradation: A green and efficient strategy for indoor air purification - Cheng Zhang; Xiaoyu Zhang; Jiqiang Liu; Qing Li; Bowen Mo; Yu Chen; Jinmeng Sun; Zeyu Tang; Wei Liu (Journal of Environmental Chemical Engineering, 2026)

Toxic effects and molecular mechanisms of Fluopyram on the liver of zebrafish (Danio rerio) - Yuqing Hou; Bo Cheng; Baihui Shi; Shuhan Li; Xuzhi Zhang; Lanjun Wang; Rui Yang; Lusheng Zhu; Jun Wang; Young Mo Kim; Jinhua Wang (Journal of Environmental Management, 2026)

Improving groundwater level prediction based on optimized deep learning model with Coati algorithm - Rana Muhammad Adnan; Jing-Cheng Han; Mo Wang; Sandeep Samantaray; Abinash Sahoo; Sajjad Firas Abdulameer; Mohammad Al-Suwaiyan; Zaher Mundher Yaseen (Environmental Modelling & Software, 2026)

Tailoring CO2 fixation through glucose and acetone as co-substrates for mevalonate biosynthesis with high carbon atom economy - Wei Lu; Wen Liu; Tao Cheng; Ruotong Chen; Mo Xian; Jing Guo; Rubing Zhang (Sustainable Chemistry and Pharmacy, 2026)

Storm surge forecasting using TCWiSE synthetic typhoons with an LSTM model - Cheng Chen; Jianxiang Mo; Hongkun Lin; Fengyi Li (Ocean Engineering, 2026)

Metal Mixture Exposure, Metabolic Networks, and Hemoglobin Reduction: A Population-Based Metabolomics Study - Ping Cheng; Ya Xie; Yuan Chen; Dandan Xu; Xinhan Zhang; Qing Liu; Runsong Zhang; Zhe Mo; Zhijian Chen; Jie Xiang; Wei Xia (Environmental Pollution, 2026)

Functional noncoding variants within the TBX1 enhancer contribute to tetralogy of Fallot - Jimiao Gao; Tao Jiang; Yingyi Quan; Xinyue Liu; Min Da; Jiang Jiang; Jun Zhou; Hao Sun; Yan Zhou; Wanting Ma; Zicheng Zhang; Yiwei Cheng; et al. (Science China Life Sciences, 2026)

Bioremediation of α-terpineol-contaminated flotation wastewater using biochar-immobilized biosurfactant-producing bacteria - Jin-Cheng Ye; Ying-Xi Liu; Huan Du; You-Qun Xie; Lei Xiang; Bai-Lin Liu; Nai-Xian Feng; Yan-Wen Li; Quan-Ying Cai; Ce-Hui Mo; Hai-Ming Zhao (Journal of Environmental Management, 2026)

Physiological Responses and Functional Performance of Eucheumatoid Seaweeds Under Prolonged Low-Salinity Stress - Jianling Zhan; Zhenwei Mo; Fen Cheng; Xianming Tang; Hong Du; Qiong Wu (Journal of Marine Science and Engineering, 2026)
Low-salinity events caused by heavy rainfall and freshwater runoff pose significant environmental constraints on eucheumatoid seaweed mariculture in coastal areas. In this study, five eucheumatoid seaweeds, including three strains of Kappaphycus alvarezii (Hn-R, Hn-G, and Ma-R), Kappaphycus striatum, and Eucheuma denticulatum, were exposed to 22, 26, and 30 psu for 36 days. Growth performance, photosynthetic pigments, chlorophyll fluorescence parameters, oxidative damage, and antioxidant responses were determined. To compare the actual physiological performance of different seaweeds under each salinity condition, a functional performance score was calculated using membership function analysis based on relative growth rate, chlorophyll a, carotenoids, photosynthesis, and malondialdehyde. Low salinity generally reduced growth, photosynthetic pigment content, and photosystem II performance, while increasing malondialdehyde content and antioxidant-related parameters, indicating that prolonged low-salinity exposure induced both physiological inhibition and oxidative stress responses. At 22 psu, K. alvarezii Ma-R showed the strongest functional performance, followed by K. striatum and E. denticulatum. At 26 psu, E. denticulatum showed the strongest functional performance, followed by K. alvarezii Ma-R and K. striatum. These results indicate that eucheumatoid seaweeds differ in their functional performance under mild and more severe low-salinity tolerance, providing physiological evidence for selecting candidate eucheumatoid seaweeds for salinity-fluctuating coastal mariculture.

Virulensome: a transient organelle mediating fungal virulence - Pei-Ji Zhao; Qian-Yi Hu; Si-Han Wang; Cheng-Song Wang; Xue-Xian Jian; Xing-Fu Wen; Yu-Lin Luo; Ya-Qi Zhang; Chun-Mei Xiang; Guo-Hong Li; Shu-Qun Liu; Ming-He Mo; et al. (Science China Life Sciences, 2026)

Precision measurement of the Ds*+-Ds+ meson mass difference - M. Ablikim; M.N. Achasov; P. Adlarson; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; Y. Ban; H.-R. Bao; V. Batozskaya; et al. (Science Bulletin, 2026)

CO2-responsive ethyl cellulose–microsphere films for postharvest freshness monitoring of fresh products - Daoyu Liu; Liangbin Hu; Enbo Xu; Huan Cheng; Hongbo Li; Dan Xu; Jiayi Zhang; Lishan Yao; Lu Tian; Xiaolin Zhu; Feilei Zhu; Jing Wang; et al. (Food Control, 2026)

Exploratory observation of dietary exogenous bile acids on growth, hepatic glucose metabolism, intestinal and liver health, and fillet quality of Monopterus albus fed high-carbohydrate diets - Jiamin Li; Peng Fang; Ao Luo; Luyao Xu; Tianlun Luo; Junzhang Han; Tingting Li; Xiaoxuan Qi; Shuo Cheng; Huanhuan Huo; Mo Peng (Animal Feed Science and Technology, 2026)

Species-specific accumulation and biomagnification of PFASs in aquatic and terrestrial organisms from the Xisha Islands - Yu-Quan Zhang; Jun Xiang; Jiao-feng Gu; Peng Zeng; Qi-Fei Peng; Yong-Fu Chen; Yu-Feng Hu; Li-cheng Wang; Hang Zhou; Ling Mo (Marine Pollution Bulletin, 2026)

Metabolomic analysis reveals the dynamic changes of metabolites during storage process in passion fruit - Chunyan Mo; Lulu Cheng; Zheng Lei; Xiang Meng; Xijin Xie; Xu Zhao; Yun Xiong (Food Chemistry, 2026)

Deciphering the molecular pathways underlying di(2-ethylhexyl) phthalate degradation and metabolic adaptation in Alexandrium pacificum - Hong-Jia Huang; Dan Huang; Jiang-Bing Qiu; Si-Ying Li; Qing Han; Cai-Qin Cheng; Hao-Yun Zhang; Zong-Di Wang; Yi-Tong Huang; Li-Gong Zou; Ce-Hui Mo; Hong-Ye Li; et al. (Journal of Hazardous Materials, 2026)

Machine learning-coupled multi-elemental fingerprinting for high-accuracy source identification of distillation residues: A novel strategy for industrial waste traceability - Yiqing Sun; Qingwei Guo; Xiubao Wang; Jianwei Yue; Xiaocheng Song; Siyuan Yang; Wei Liu; Ling Mo; Li-Cheng Wang; Lingshuai Kong; Jinhua Zhan; Zhenhui Gao (Journal of Hazardous Materials, 2026)

Silkworm excrement–immobilized bacteria for synergistic remediation of phthalate esters in agricultural soil - Yong-Hong Chen; Huan Du; Ying-Xi Liu; Ke Xu; Jin-Cheng Ye; Bai-Lin Liu; Nai-Xian Feng; Lei Xiang; Yan-Wen Li; Quan-Ying Cai; Ce-Hui Mo; Hai-Ming Zhao (Journal of Hazardous Materials, 2026)

Subchronic exposure of tire wear particles leachate induces oxidative stress and DNA damage in zebrafish (Danio rerio) brain - Bo Cheng; Yurui Hou; Yuqing Hou; Lanjun Wang; Yibo Gao; Yuhan Ye; Tao Tang; Baihui Shi; Junpu Wang; Lusheng Zhu; Jun Wang; Young Mo Kim; et al. (Journal of Environmental Management, 2026)

Mechanistic insights into the stereoselective toxicity of chiral difenoconazole in HepG2 cells - Xuzhi Zhang; Yuchen Guo; Junpu Wang; Yuqing Hou; Lanjun Wang; Shuhan Li; Bo Cheng; Lusheng Zhu; Jun Wang; Young Mo Kim; Jinhua Wang (Journal of Environmental Management, 2026)

Occurrence, landscape impact, and risk assessments of pesticides in a major river basin of a tropical island, South China - Ling Mo; Bin Tang; Li-Ke Chen; Jun Xiang; Ming-Yang Wang; Kai-Yi Wu; Ming-Zhong Ren; Qiao Xing; Li-Cheng Wang; Jing Zheng (Environmental Pollution, 2026)

Orchestrating Ovarian Dysfunction- The Role of Programmed Cell Death in PCOS - Yuhua Chen; Di Cheng; Zhongcheng Mo; Yuanjie Xie; Siquan Wen; Yi Tan (Cell Biochemistry and Biophysics, 2026)

A CPTu-based method for evaluating consolidation characteristics of under-consolidated soils - Yu-cheng Li; Pin-Qiang Mo; Guojun Cai; Zhao Lu; Yan Zhuang; Hai-Sui Yu (Ocean Engineering, 2026)

Lactiplantibacillus pentosus JWN01 and Lactiplantibacillus plantarum JWN02 attenuate renal fibrosis and pathological autophagy in hyperuricemic nephropathy via gut–kidney axis - Qizhou Mo; Min Qin; Haiqi Liang; Liwei Wei; Yujian Li; Yangmei Qin; Lichun Tang; Jing Liang; Chong Qian; Yilong Liang; Shufeng Luo; Yutuo Wei; et al. (Food Research International, 2026)

Coral mucus input promotes sedimentary organic matter degradation: Evidence from a typical coral reef area, northern South China Sea - Bo Yang; Bin Yang; Lei Xie; Zhenjun Kang; Xiaorong Mo; Qin Li; Jiaodi Zhou; Haifang Huang; Tingting Yan; Cheng Xu (Environmental Research, 2026)

Interfacial dipolar channels of high-dielectric BaTiO3/PVDF composite film enable high-rate and stable lithium batteries - Luozhi Mo; Enmin Xu; Yingke Zhou; Xuan Liu; Zhe Cheng; Xiaohui Tian (Chemical Engineering Journal, 2026)

Development and Evaluation of Antioxidant Postbiotics from Bacillus amyloliquefaciens C-1 to Alleviate DSS-Induced Colitis - Xinyao Hou; Jiayu Feng; Jiale Qin; Jianhui Mo; Rong Yu; Jia Lv; Shaoru Li; Jing Tian; Yue Cheng; Bei Han (Probiotics and Antimicrobial Proteins, 2026)

Consolidation characteristics of diatomaceous soil in coastal reclamations revealed by CPTu tests - Pin-Qiang Mo; Yu-cheng Li; Guojun Cai; Qiuzhu Ma; Hai-Sui Yu (Engineering Geology, 2026)

A novel pathologic scoring system for predicting postoperative recurrence in BCLC stage 0-A hepatocellular carcinoma patients: a nationwide multicenter study - Feng Xia; Jing Yan; Xulin Liu; Zhao Huang; Zhancheng Qiu; Qiao Zhang; Zhenheng Wu; Zhiyuan Huang; Renjie Wei; Li Lin; Liping Liu; Shuangqin Han; et al. (Science China Life Sciences, 2026)

High-throughput screening identifies paullinic acid as an antiviral agent against Bombyx mori nucleopolyhedrovirus - Zhenwei Jia; Xiaoli Mo; Shidong Jiang; Li Sui; Yiling Zhang; Xueyang Wang; Jie Cheng; Ping Qian; Xudong Tang (Pesticide Biochemistry and Physiology, 2026)

Facile molten salt synthesis of Co@N-C catalysts enables highly efficient HMF-to-FDCA conversion under mild conditions - Hao-Yue Ma; Jun-Fei Gu; Xing-Chuan Li; Zhan Chen; Qi-Yu Fu; Francis Verpoort; Wen-Jie Mo; Zheng Liu; Cheng Chen; Soon Hyeok Hong; Zongkui Kou (Chemical Engineering Journal, 2026)

Liquid-like PDMS brushes/TiO2 microcapsule-driven coatings with integrated self-healing, photodegradation, and antifouling functions - Jingjing Ren; Taolin Zhang; Shouzheng Jiao; Fanghua Pan; Jingru Sun; Ran Mo; Yuwei Hao; Zhengyu Chen; Siqiao Zhang; Zhicheng Sun; Zhongjun Cheng (Journal of Environmental Chemical Engineering, 2025)

Comparative study of hydrochemical characteristics and formation mechanisms of representative geothermal areas in Xinjiang area, Northwest China - Jiangyun Wang; Mo Xu; Chengpeng Ling; Haojie Cheng; Heng Zhang; Jian Guo (Geothermics, 2025)

Construction of alkali-induced rice protein/konjac glucomannan hydrogel and its application in gel candy - Jing Zhang; Xiangrui Li; Wenfei Xiong; Yijun Yao; Cheng Mo; Weikang Cao; Lifeng Wang (Food Chemistry, 2025)

Self-repair mechanisms of spiking neuron–astrocyte networks in working memory under diverse injury conditions - Bingyi Mo; Xiaoqian Liu; Lin Li; Shanshan Cheng; Yuan Zhu; Ming Yi; Lulu Lu (Cognitive Neurodynamics, 2025)

Enhanced bioremediation of α-terpineol-contaminated mining soil through immobilization of Indigenous biosurfactant-producing bacteria on biochar - Jin-Cheng Ye; Wei-Liang Li; You-Qun Xie; Huan Du; Lei Xiang; Bai-Lin Liu; Nai-Xian Feng; Yan-Wen Li; Quan-Ying Cai; Miaoyue Zhang; Ce-Hui Mo; Hai-Ming Zhao (Biology and Fertility of Soils, 2025)

Per- and polyfluoroalkyl substances in tissues of intermediate egrets (Ardea intermedia) from the South China Sea - Ling Mo; Jun Xiang; Ming-Yang Wang; Yu-Quan Zhang; Qin-Wei Hao; Qi-Fei Peng; Yong-Fu Chen; Yu-Feng Hu; Jing Zheng; Qiao Xing; Bin Tang; Li-Cheng Wang (Marine Pollution Bulletin, 2025)

Sense of security in age-friendly cities: Exploring the trade-off between the supply and demand for elderly care services in Hong Kong - Kar Him Mo; Tian Cheng; Izzy Yi Jian; Weixuan Chen (Sustainable Cities and Society, 2025)

Adsorption-desorption behavior of difenoconazole onto soils: Kinetics, isotherms, and influencing factors - Baihui Shi; Wenjie Zhang; Cheng Xiu; Lanjun Wang; Yuqing Hou; Shengfang Wen; Yuchen Guo; Jun Wang; Lusheng Zhu; Zhijiang Lu; Young Mo Kim; Jinhua Wang (Pesticide Biochemistry and Physiology, 2025)

Comparative metabolomics profiling reveals the aroma and nutritional diversity of eight wild edible plants - Lulu Cheng; Chunyan Mo; Peijie Ma; Yajiao Li; Yun Xiong (Food Chemistry, 2025)

Assessing scale-dependent urban wind loss patterns: A CFD analysis of realistic urban segments from 1980 to 2020 - Ran Wang; Ziwei Mo; Di Mei; Wai-Chi Cheng; Kangcheng Zhou; Chun-Ho Liu (Sustainable Cities and Society, 2025)

Albumin mediates the association between maternal exposure to multiple metals and gestational diabetes mellitus: Findings from the Guangxi Birth Cohort Study - Hualong Qiu; Yu Bao; Shengzhu Huang; Yuen Zhong; Caitong He; Long Tian; Yu Zhang; Bangzhu Luo; Tao Liang; Baohong Pang; Mujun Li; Hong Cheng; et al. (Journal of Trace Elements in Medicine and Biology, 2025)

Phase change nanoemulsions developed by a modified phase inversion temperature method for low-temperature thermal energy storage - Songping Mo; Wenke Cheng; Junhao Chen; Yuxuan Lin; Zicai Pan; Zhi Yang; Lisi Jia; Yanping Du; Ying Chen (International Journal of Refrigeration, 2025)

Mapping drag coefficient using CFD and machine learning with application to urban canopy model - Jie Chen; Ziwei Mo; Congyu Li; Wai-Chi Cheng; Chun-Ho Liu (Sustainable Cities and Society, 2025)

Catalytic fast pyrolysis of waste battery separators with limited removal of the Al2O3 layer for selective aromatic hydrocarbons production over HZSM-5 catalyst - Li Zhao; Wan-zhao Huang; Shi-guan Yang; Qi Niu; Shi-yu Feng; Pu-cheng Wang; Ying Mo; Yu-han Fan; Kai Li; Qiang Lu (Journal of Environmental Management, 2025)

Comprehensive identification of crucial biomarkers and therapeutic targets in cholestasis via integrated single-cell RNA and transcriptome sequencing analysis - Cichun Wu; Da Cheng; Juan Mo; Nianqi Zhou; Shifang Peng; Lei Fu (Mammalian Genome, 2025)

A candidate multi-epitopes vaccine against encephalomyocarditis virus confers protection in mice - Hongshan Li; Rongrong Cheng; Pingan Dong; Yongfang Chen; Rongqian Mo; Jiayu Yue; Dianyu Li; Yanmei Yang; Amjad Ali; Xiangrong Li; Ruofei Feng (Veterinary Microbiology, 2025)

Screening and discovery of volatile allergenic components from artemisia ordosica in Yulin region of Northern China - Xiaoxue Mo; Cheng Wang; Yi Shan; Siqi Wang; Wen Yang; Zhaomin Xia; Zhanguo Qiao; Tao Zhang; Yuanyuan Ding; Rui Liu; Huaizhen He; Langchong He (Journal of Hazardous Materials, 2025)

Sustainable remediation of butyl xanthate-contaminated mine wastewater by combining emergent macrophyte Cyperus alternifolius with a versatile bacterial isolate - Qi Liu; Yao-Yao Ye; Sha Yang; Cheng-Yu Cui; Huan Du; Jin-Cheng Ye; Ji-Liang Cheng; Rui-Wen Hu; Lei Xiang; Bai-Lin Liu; Yan-Wen Li; Quan-Ying Cai; et al. (Journal of Hazardous Materials, 2025)

Removal of Microcystis aeruginosa using hydrodynamic cavitation in a jet pump cavitation reactor: Considering the mechanical and chemical effects - Tongshan Chai; Xiaoyu Mo; Shuangjie Xu; Huaiyu Cheng; Xinping Long; Zuti Zhang (Journal of Environmental Management, 2025)

Influence of the triazole fungicide difenoconazole on soil microbial communities, antibiotic resistance genes, and pathogens - Baihui Shi; Wenjie Zhang; Lanjun Wang; Changrui Liu; Junpu Wang; Bo Cheng; Lusheng Zhu; Young Mo Kim; Jinhua Wang (Applied Soil Ecology, 2025)

Encephalomyocarditis virus non-structural protein 2C induces the degradation of NDP52 autophagy protein to promote its own survival - Rongqian Mo; Rongrong Cheng; Pingan Dong; Tingting Ma; Yaxin Zhang; Jingying Xie; Shasha Li; Huixia Li; Adi Idris; Xiangrong Li; Ruofei Feng (Veterinary Microbiology, 2025)

Unveiling Impact of Polyamide Microplastics on Ceftiofur Sodium Migration in Porous Media: Experimental and Modeling Insights - Yanna Chen; Ming Wu; Zhou Cheng; Yanru Hao; Cehui Mo; Qusheng Li; Jianfeng Wu; Jichun Wu; Bill X. Hu (Water, Air, & Soil Pollution, 2025)

G6PD lactylation is involved in regulating redox balance of boar sperm in low glucose extender - Jia Cheng; Qiqi Dong; Saiya Nie; Xu Hao; Sha Mo; Yixing Liu; Zhendong Zhu; Hongzhao Lu; Tao Zhang; Wenxian Zeng (Theriogenology, 2025)

Modeling and mechanistic understanding of vertical dissolved methane transport in integrated vertical flow constructed wetlands (IVCWs) - Ru Xue; Ke Zhang; Xiaoling Liu; Bing Jiang; Hongbing Luo; Mei Li; You Mo; Cheng Liu; Lin Li; Wei Chen; Lin Cheng; Jia Chen; et al. (Journal of Water Process Engineering, 2025)

Species-specific bioaccumulation and biotransformation of two novel brominated flame retardants in fish: Insights from isotope fractionation - Ling Mo; Guang-Yu Liao; Bin Tang; Cheng-Zhong Fu; Dong-Jing Zhou; Dong-Wei Du; Wei-Keng Luo; Rong-Fa Xu; Ming-Zhong Ren; Jing Zheng (Environmental Research, 2025)

RNA-binding protein expression based machine learning model predicts metastasis and treatment outcome of testicular cancer - Lin-jian Mo; Hai-qi Liang; Zhen-yuan Yu; Yao-wen Liang; Chuan-xin Gu; Qiu-ju Wei; Qi-huan He; Fa-ye Wei; Ji-wen Cheng; Zeng-nan Mo (Genes & Genomics, 2025)

6PPD impairs immune responses and fin regeneration in zebrafish - Xiaoyu Mao; Dashuang Mo; Yuqin Cheng; Mengzhu Lv (Toxicology Letters, 2025)

Atmospheric nitrogen deposition has minor impacts on the abundance and diversity of arbuscular mycorrhizal fungi and their contribution to soil carbon stock in tropical forests - Andi Li; Peter Meidl; Senhao Wang; Bo Tang; Matthias C. Rillig; Guangcan Yu; Jing Chen; Rongzhen Liu; Zhiyang Lie; Anchi Wu; Lili Rong; Cheng Peng; et al. (Soil Biology and Biochemistry, 2025)

CTHRC1 expresses in cancer-associated fibroblasts and is associated with resistance to anti-androgen therapy in prostate cancer - Hai-qi Liang; Qi-huan He; Qiu-ju Wei; Qi-zhou Mo; Guang-lin Yang; Fa-ye Wei; Li-wei Wei; Yu-jian Li; Min Qin; Ji-wen Cheng (Genes & Genomics, 2025)

2-Aminoethyl diphenylborinate mitigates damage from the endoplasmic reticulum of vitrified bovine oocyte - Xianhong Mo; Rong Liang; Cheng Guo; Zengyuan Zhao; Jing Zhao; Yi Fang; Zhenjun Xu (Theriogenology, 2025)

Towards sustainable development: The role of the carbon emission trading scheme in improving energy enterprises' carbon performance - Xiao-Jun Cheng; Xin-Wei Li; Hai Wang; Mo Guo (Journal of Environmental Management, 2025)

RNA Binding Protein IGF2BP3 Rehabilitates Glycolysis of Vascular Endothelial Cells to Protect the ox-LDL-induced Cellular Injury via Stabilizing LDHA mRNA - Xing-Chun Mo; Ping Lu; Qu-Cheng Wei; Xiao-Jing Yang (Cell Biochemistry and Biophysics, 2025)

The role of liver sinusoidal endothelial cells in metabolic dysfunction-associated steatotic liver diseases and liver cancer: mechanisms and potential therapies - Hanjun Mo; Pengfei Yue; Qiaoqi Li; Yinxi Tan; Xinran Yan; Xinyue Liu; Yuanwei Xu; Yingzhe Luo; Suruiya Palihati; Cheng Yi; Hua Zhang; Minlan Yuan; et al. (Angiogenesis, 2025)

Measurement of the decay Ξ 0 → Λ γ with entangled Ξ 0 Ξ ¯ 0 pairs - M. Ablikim; M.N. Achasov; P. Adlarson; O. Afedulidis; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; I. Balossino; Y. Ban; et al. (Science Bulletin, 2025)

Influence of precipitation and temperature variability on anthropogenic nutrient inputs in a river watershed: Implications for environmental management - Shuhui Zhang; Xia Li; Ze Ren; Cheng Zhang; Le Fang; Xiaobiao Mo; Wei Yang; Xinhui Liu (Journal of Environmental Management, 2025)

Identification and pharmacological characterization of pH-sensitive chloride channels in the fall armyworm, Spodoptera frugiperda - Wei Wang; Jia-Sheng Chen; Pei-Yun He; Mo-Han Zhang; Hai-Qun Cao; Subba Reddy Palli; Cheng-Wang Sheng (Insect Biochemistry and Molecular Biology, 2025)

Cascading effect modelling of integrating geographic factors in interdependent systems - Yong Ge; Mo Zhang; Rongtian Zhao; Die Zhang; Zhiyi Zhang; Daoping Wang; Qiuming Cheng; Yuxue Cui; Jian Liu (Environmental Modelling & Software, 2025)

The trojan horse strategy in T-ALL therapy by engineering T-ALL-derived exosomes for targeted delivery of Isoliquiritigenin to the bone marrow to conquer Drug-Resistant T-ALL in PDX model - Yong Liu; Lindi Li; Cheng Ouyang; Zefan Du; Su Liu; Hailin Zou; Chunmou Li; Junbin Huang; Yucai Cheng; Mengyao Tian; Tianwen Li; Jiani Mo; et al. (Chemical Engineering Journal, 2025)

Establishing patient-derived tumor organoids of bone metastasis from lung adenocarcinoma reveals the transcriptomic changes underlying denosumab treatment - Xianglin Hu; Huajian Wu; Kewen Hu; Yani Kang; Guoqiang Hua; Mo Cheng; Wangjun Yan; Wending Huang (Clinical & Experimental Metastasis, 2025)

6PPD induces cerebrovascular defects by triggering oxidative stress and ferroptosis in zebrafish - Mengzhu Lv; Xiaoyu Mao; Zheng Lu; Yanzhu Yang; Jiangtao Huang; Yuqin Cheng; Chuan Ye; Zhixu He; Liping Shu; Dashuang Mo (Science of The Total Environment, 2025)

Comprehensive metabolome and transcriptome analyses shed light on the regulation of SlNF-YA3b in carotenoid biosynthesis in tomato fruit - Peiwen Wang; Siyu Ran; Yuanhang Xu; Fulei Mo; Fengshuo Li; Rui Lv; Fanyue Meng; Huixin Zhang; Yuxin Zou; Lei Yu; Tianyue Yu; Mozhen Cheng; et al. (Postharvest Biology and Technology, 2025)

A quadrature element formulation of geometrically exact thin-walled beam with deformable cross-section - Run Zhang; Jiahao Cheng; Shuzhen Mo; Hongzhi Zhong (Engineering Structures, 2025)

Map-based cloning revealed BhAPRR2 gene regulating the black peel formation of mature fruit in wax gourd (Benincasa hispida) - Xuling Zhai; Jinqiang Yan; Wenrui Liu; Zheng Li; Zhenqiang Cao; Ying Deng; Renlian Mo; Baochen Wang; Xiaoxin Cheng; Dasen Xie; Biao Jiang (Theoretical and Applied Genetics, 2025)

Two new species of the subgenus Tipula (Emodotipula) Alexander, 1966 (Diptera, Tipulidae) from southwest China - Qi-Cheng Yang; Li-Ling Mo; Jing Wang; Xiao-Yan Liu; Ding Yang (Journal of Asia-Pacific Entomology, 2024)

European bilberry extract reduces high-temperature baked food-induced accumulation of Nε-carboxymethyllysine and Nε-carboxyethyllysine in vivo - Xiaoxing Mo; Lihui Shen; Xinyu Wang; Yunhong Sun; Ruijie Cheng; Wenwen Chen; Juan Chen; Ruikun He; Liegang Liu (Food Research International, 2024)

Metal-ion-binding properties of glycyrrhiza polysaccharide extracted from Licorice: Structural characterization and potential application in drug delivery - Yanjun Yang; Mengli Yu; Yulin Mo; Yue Cheng; Bin Huang; Weilin Wang; Maomao Zhu; Xiaobin Jia; Liang Feng; Bing Yang (Carbohydrate Polymers, 2024)

Optimizing ABA-based chemically induced proximity for enhanced intracellular transcriptional activation and modification response to ABA - Zeng Zhou; Yue-Qi Wang; Xu-Nan Zheng; Xiao-Hong Zhang; Lu-Yao Ji; Jun-You Han; Ze-Cheng Zuo; Wei-Liang Mo; Li Zhang (Science China Life Sciences, 2024)

Mycobacterium marinum mediates regulation of prostaglandin E2 expression on host immune response through cyclooxygenase pathway - Dongzi Lin; Bingyao Lin; Xuezhi Wang; Cheng Xu; Liyi Mo; Yanwen Luo; Honghong Tian; Lei Zhou; Zhenhua Chen (Molecular Biology Reports, 2024)

Integrating carbon and water footprint into nature-based solution (NBS) for urban planning in a highly built-up area in Guangzhou, China - Mo Wang; Xu Zhong; Haojun Yuan; Dongqing Zhang; Liang Cheng; Jie Zhang (Science of The Total Environment, 2024)

PM2.5 constituents associated with mortality and kidney failure in childhood-onset lupus nephritis: A 19-year cohort study - Guohua He; Yaqi Wang; Cheng Cheng; Jianhui Guo; Zhilang Lin; Ziyun Liang; Bei Jin; Liyuan Tao; Liping Rong; Lizhi Chen; Tianxin Lin; Yining Hua; et al. (Science of The Total Environment, 2024)

Evaluation and comparison of iohexol elimination by UV/peroxymonosulfate and UV/persulfate processes: Radical roles, influence factors and iodinated trihalomethanes formation - Chen-Cheng Mo; Fu-Xiang Tian; Bin Xu; Fan Lai; Yu-Qiong Gao; Yan Ma; Zi-Han Feng; Zi-Jian Yao; Dong-Su Bi; Xiao-Jun Hu (Journal of Water Process Engineering, 2024)

Isolation and characterization of Bifidobacterium spp. from breast milk with different human milk oligosaccharides utilization and anti-inflammatory capacity - Xinxin Ma; Jianhui Mo; Lu Shi; Yue Cheng; Jiayu Feng; Jiale Qin; Wanghong Su; Jia Lv; Shaoru Li; Qiang Li; Hui Tan; Bei Han (Food Research International, 2024)

A novel strategy employing lignin biochar to simultaneously promote remediation and safe crop production in Cd-contaminated soil - Yanying He; Baobin Mi; Cheng Luo; Honglin Tao; Xin Zhang; Jinwen Yu; Xueying Mo; Jian Hu; Long Chen; Naimei Tu; Fangfang Wu (Chemical Engineering Journal, 2024)

Improving key gene expression and di-n-butyl phthalate (DBP) degrading ability in a novel Pseudochrobactrum sp. XF203 by ribosome engineering - Yunchang Xie; Nai-Xian Feng; Li Huang; Miaoer Wu; Cheng-Xuan Li; Fantao Zhang; Yunhong Huang; Quan-Ying Cai; Lei Xiang; Yan-Wen Li; Hai-Ming Zhao; Ce-Hui Mo (Science of The Total Environment, 2024)

Cascade effects of global supply chains induced by regional conflicts increase global inequality - Rongtian Zhao; Daoping Wang; Yong Ge; Mo Zhang; Die Zhang; D'Maris Coffman; Qiuming Cheng (Resources, Conservation and Recycling, 2024)

Impact of diatomit on the transport behavior of unmodified and carboxyl-modified nanoplastics in saturated porous media - Yuheng Wu; Ming Wu; Zhou Cheng; Yanru Hao; Cehui Mo; Qusheng Li; Jianfeng Wu; Jichun Wu; Bill X. Hu; Guoping Lu (Environmental Pollution, 2024)

Matrine inhibits invasion and migration of gallbladder cancer via regulating the PI3K/AKT signaling pathway - Rong-Liang Mo; Zhuang Li; Peng Zhang; Ming-Hui Sheng; Gen-Cheng Han; Deng-Qun Sun (Naunyn-Schmiedeberg's Archives of Pharmacology, 2024)

Insights into in situ surface reconstruction in cobalt perovskite oxides for enhanced catalytic activity - Yanyu Jin; Hongjun Cheng; Qibao Wang; Xiaoqing Liu; Shengpeng Mo; Bin Zhou; Yue Peng; Yu Wang; Wenzhe Si; Junhua Li (Journal of Hazardous Materials, 2024)

Development of a facile one-pot synthesized fluorescent green polyesters as cooling water antiscalants for industrial application - Lijun Gao; Tianming Gao; Jiuying Feng; Shaohong Mo; Yanbei Guo; Pingping Guo; Shiyun Pan; Yuqing Cheng; Qian Yang (Desalination, 2024)

Wearable solid-phase microextraction sampling for enhanced detection of volatile analytes in human ears - Wenzheng Mo; Lei Li; Bi-Cheng Yang; Xiangjie Wang; Baixue Wang; Jianfeng Zhang; Qiaoyun Huang; Zhong-Ping Yao; Dong Zhang; Bin Hu (Analytica Chimica Acta, 2024)

The origins of odor (β-cyclocitral) under different water nutrient conditions: Algae or submerged plants? - Yu Lin; Chaoyue Cheng; Yutai Dai; Weijie Li; Jiping Chen; Mo Chen; Ping Xie; Qiang Gao; Xiaoyue Fan; Xuwei Deng (Science of The Total Environment, 2024)

Carbon and hydrogen isotopic compositions of C7 hydrocarbons and their geochemical significance in light oils/condensates from the Kuqa Depression, Tarim Basin, NW China - Qinghua Wang; Hanyu Deng; Tao Mo; Haizu Zhang; Bin Cheng; Yunpeng Wang; Zewen Liao (Organic Geochemistry, 2024)

Re-melting of the Neoproterozoic juvenile mafic lower crust: The origin of adakitic and non-adakitic felsic suites in the southwest margin of Yangtze Craton - Jingkai Wu; Zhidan Zhao; Xiaowei Li; Xuejing Tu; Chen Li; Hangshan Lei; Qian Ma; Zhuang Miao; Yiyun Yang; Dong Liu; Qing Wang; Di-Cheng Zhu; et al. (Lithos, 2024)

Significance of non-DLVO interactions on the co-transport of levofloxacin and titanium dioxide nanoparticles in porous media - Yiqun Cui; Ming Wu; Guoping Lu; Zhou Cheng; Meng Chen; Yanru Hao; Cehui Mo; Qusheng Li; Jianfeng Wu; Jichun Wu; Bill X. Hu (Environmental Pollution, 2024)

Crosstalk among proximal tubular cells, macrophages, and fibroblasts in acute kidney injury: single-cell profiling from the perspective of ferroptosis - Yulin Wang; Ziyan Shen; Shaocong Mo; Han Zhang; Jing Chen; Cheng Zhu; Shiqi Lv; Di Zhang; Xinhui Huang; Yulu Gu; Xixi Yu; Xiaoqiang Ding; et al. (Human Cell, 2024)
The link between ferroptosis, a form of cell death mediated by iron and acute kidney injury (AKI) is recently gaining widespread attention. However, the mechanism of the crosstalk between cells in the pathogenesis and progression of acute kidney injury remains unexplored. In our research, we performed a non-negative matrix decomposition (NMF) algorithm on acute kidney injury single-cell RNA sequencing data based specifically focusing in ferroptosis-associated genes. Through a combination with pseudo-time analysis, cell–cell interaction analysis and SCENIC analysis, we discovered that proximal tubular cells, macrophages, and fibroblasts all showed associations with ferroptosis in different pathways and at various time. This involvement influenced cellular functions, enhancing cellular communication and activating multiple transcription factors. In addition, analyzing bulk expression profiles and marker genes of newly defined ferroptosis subtypes of cells, we have identified crucial cell subtypes, including Egr1 + PTC-C1, Jun + PTC-C3, Cxcl2 + Mac-C1 and Egr1 + Fib-C1. All these subtypes which were found in AKI mice kidneys and played significantly distinct roles from those of normal mice. Moreover, we verified the differential expression of Egr1, Jun, and Cxcl2 in the IRI mouse model and acute kidney injury human samples. Finally, our research presented a novel analysis of the crosstalk of proximal tubular cells, macrophages and fibroblasts in acute kidney injury targeting ferroptosis, therefore, contributing to better understanding the acute kidney injury pathogenesis, self-repairment and acute kidney injury-chronic kidney disease (AKI-CKD) progression.

Molecular insights into the catabolism of dibutyl phthalate in Pseudomonas aeruginosa PS1 based on biochemical and multi-omics approaches - Huan Du; Ji-Liang Cheng; Zhi-Yong Li; Huai-Ning Zhong; Shuang Wei; Yu-Juan Gu; Can-Can Yao; Miaoyue Zhang; Quan-Ying Cai; Hai-Ming Zhao; Ce-Hui Mo (Science of The Total Environment, 2024)

A wireless fluorescent sensing device for on-site closed-loop detection of hydrazine levels in the environment - Zihao Zhu; Ke Song; Xiaobai Li; Yu Chen; Fanwei Kong; Wanqi Mo; Zhiyong Cheng; Shilong Yang; Hongwei Ma (Journal of Hazardous Materials, 2024)

Efficient trimethoprim removal via cooperation of radical and non-radical pathways in UV/peroxymonosulfate: Kinetics, mechanisms and disinfection by-products-associated risks - Chen-Cheng Mo; Fu-Xiang Tian; Bin Xu; Juan Wang; Yu-Qiong Gao; Dong-Su Bi; Bo Wang; Xing-Yan Mu; Xiao-Jun Hu (Journal of Environmental Chemical Engineering, 2024)

Membrane–protected magnetic covalent organic framework for efficient extraction of estrogens in dairy products - Cheng Yang; Zheng–Lian Mo; Qiu–Fang Zhang; Jin–Jie Xu; Xiao–Fang Shen; Yue–Hong Pang (Food Chemistry, 2024)

A holistic approach to projecting streamflow and analyzing changes in ecologically relevant hydrological indicators under climate and land use/cover change - Yang Liu; Feng Liu; Cheng Chen; Qiuwen Chen; Jianyun Zhang; Kangle Mo; Qinghu Jiang; Siyang Yao (Journal of Hydrology, 2024)

Regulation of interfacial polymerization by organic base for high-permselective nanofiltration - Huiying Ding; Yuting Liu; Zhong Zhang; Yanjun Cheng; Jiahao Mo; Lu Elfa Peng; Cheng Xiang; Hongchang Pei; Xianhui Li (Desalination, 2024)

Bright long persistent luminescence in cluster-based MOFs derived from intra-ligand charge transfer characteristic - Jun-Ting Mo; Zheng Wang; Xian-Yan Xu; Fenske Dieter; Mei Pan; Cheng-Yong Su (Chemical Engineering Journal, 2024)

Contrasting range changes of Bergenia (Saxifragaceae) species under future climate change in the Himalaya and Hengduan Mountains Region - Li Qiu; Qing-Li Fu; Hans Jacquemyn; Kevin S. Burgess; Jia-Jing Cheng; Zhi-Qiong Mo; Xiao-Dong Tang; Bo-Yun Yang; Shao-Lin Tan (Theoretical and Applied Climatology, 2024)

Insights into the molecular network underlying phytotoxicity and phytoaccumulation of ciprofloxacin - Hai-Ming Zhao; He-Biao Huang; Zhen-Xuan Zhan; Yao-Yao Ye; Ji-Liang Cheng; Lei Xiang; Yan-Wen Li; Quan-Ying Cai; Yunchang Xie; Ce-Hui Mo (Science of The Total Environment, 2024)

Highly efficient Ni(II) adsorption by industrial lignin-based biochar: a pivotal role of dissolved substances within biochar - Yanying He; Qianyi Deng; Liwen Cao; Cheng Luo; Wenjie Zhao; Honglin Tao; Long Chen; Yule Zhu; Jing Zhang; Xueying Mo; Baobin Mi; Fangfang Wu (Environmental Science and Pollution Research, 2024)

Quantification and visualization of groundwater contamination prevention regionalization based on analytic hierarchy process method (AHP) in Guangdong-Hong Kong-Macao Greater Bay Area, South China - Zhou Cheng; Guoping Lu; Ming Wu; Zhaohui Li; Yirong Deng; Jinzhe Wu; Yanru Hao; Cehui Mo; Qusheng Li; Jianfeng Wu; Jichun Wu; Bill X. Hu (Journal of Hydrology, 2024)

Ecosystem health evaluation of urban rivers based on multitrophic aquatic organisms - Zhen Cui; Wenting Fan; Cheng Chen; Kangle Mo; Qiuwen Chen; Qiang Zhang; Rong He (Journal of Environmental Management, 2024)

Genetic identification of light oils and condensates using δD indices of C7 hydrocarbons: A case study in the Tarim Basin, NW China - Hanyu Deng; Haizu Zhang; Yiman Zhang; Naidong Chen; Tao Mo; Bin Cheng; Zewen Liao (International Journal of Coal Geology, 2023)

Efficient removal of uranium under strong acid based on charge separation and protonation coupled covalent organic frameworks - Shun-Mo Yi; Cheng-Rong Zhang; Xin Liu; Xiao-Juan Chen; Jia-Xin Qi; Cheng-Peng Niu; Jin-Lan Liu; Ru-Ping Liang; Jian-Ding Qiu (Chemical Engineering Journal, 2023)

Quantification of two-site kinetic transport parameters of polystyrene nanoplastics in porous media - Yuheng Wu; Zhou Cheng; Ming Wu; Yanru Hao; Guoping Lu; Cehui Mo; Qusheng Li; Jianfeng Wu; Jichun Wu; Bill X. Hu (Chemosphere, 2023)

Floodwater utilization potential assessment of China based on improved conceptual model and multi-reservoir basin assessment method - Kun Wang; Zongzhi Wang; Jing Xu; Yuming Mo; Liang Cheng; Ying Bai; Huihua Du; Kelin Liu (Journal of Hydrology, 2023)

Multi-valent mRNA vaccines against monkeypox enveloped or mature viron surface antigens demonstrate robust immune response and neutralizing activity - Niubing Zhang; Xiang Cheng; Yilong Zhu; Ouyang Mo; Huiqing Yu; Liqi Zhu; Juan Zhang; Linlin Kuang; Ying Gao; Ruiyuan Cao; Xiaozhen Liang; Haikun Wang; et al. (Science China Life Sciences, 2023)

Multi-sensor imaging of winter buried lakes in the Greenland Ice Sheet - Lei Zheng; Lanjing Li; Zhuoqi Chen; Yong He; Linshan Mo; Dairong Chen; Qihan Hu; Liangwei Wang; Qi Liang; Xiao Cheng (Remote Sensing of Environment, 2023)

Black phosphorus quantum dots induced ferroptosis in lung cell via increasing lipid peroxidation and iron accumulation - Liangding Dou; Rong Liu; Zhaojizhe Wang; Zhi Huang; Lei Wang; Mo Lin; Xin Hou; Jinwen Zhang; Tantan Cheng; Qi He; Dai Wang; Dongbei Guo; et al. (Food and Chemical Toxicology, 2023)

Nano-Priming with La2O3 Improves Early Growth and Regulates Physio-Biochemical Mechanisms in Fragrant Rice Against Cadmium Toxicity - Feiyang Sun; Weifen Chen; Yong Ren; Siren Cheng; Umair Ashraf; Jiewen Zheng; Li Lin; Yixian Ma; Xiangru Tang; Zhaowen Mo (Journal of Soil Science and Plant Nutrition, 2023)

Sex disparity in cognitive aging related to later-life exposure to ambient air pollution - Shaocai Mo; Yaqi Wang; Minjin Peng; Qun Wang; Hao Zheng; Yu Zhan; Zongwei Ma; Zhiming Yang; Linjiong Liu; Kejia Hu; Jian Cheng; Yao Yao; et al. (Science of The Total Environment, 2023)

Bioremediation of aniline aerofloat wastewater at extreme conditions using a novel isolate Burkholderia sp. WX-6 immobilized on biochar - Jin-Cheng Ye; Qiu-Shi Zhao; Jin-Wei Liang; Xiao-Xiao Wang; Zhen-Xuan Zhan; Huan Du; Ji-Liang Cheng; Lei Xiang; Nai-Xian Feng; Bai-Lin Liu; Yan-Wen Li; Hui Li; et al. (Journal of Hazardous Materials, 2023)

Variations of methane fluxes and methane microbial community composition with soil depth in the riparian buffer zone of a sponge city park - Ru Xue; Ke Zhang; Xiaoling Liu; Bing Jiang; Hongbing Luo; Mei Li; You Mo; Cheng Liu; Lin Li; Liangqian Fan; Wei Chen; Lin Cheng; et al. (Journal of Environmental Management, 2023)

Compound-specific radiocarbon analysis of benzene polycarboxylic acids for source apportionment of polyaromatic organic matter in ambient aerosols - Xin Yi; Xiaofei Geng; Yangzhi Mo; Guangcai Zhong; Jiao Tang; Sanyuan Zhu; Zhineng Cheng; Shizhen Zhao; Jun Li; Örjan Gustafsson; Ping'an Peng; Gan Zhang (Atmospheric Environment, 2023)

Temporal microbial succession drives phase-dependent kinetics of di(2-ethylhexyl) phthalate biodegradation in soil - Ruiwen Hu; Songfeng Liu; Haiming Zhao; Zhigang Wang; Longfei Shu; Jiaxiong Zeng; Quanying Cai; Cehui Mo; Zhili He; Cheng Wang (Biology and Fertility of Soils, 2023)

Void fraction research and destructive examination of CFETR toroidal field coil protype joints - Yue Xu; Kun Lu; Guang Shen; Bing Hu; Feng Cheng; Chao Mo; Mengyuan Zhang; Yanyu Xie (Annals of Nuclear Energy, 2023)

Global depth distribution of belowground net primary productivity and its drivers - Liujun Xiao; Guocheng Wang; Jinfeng Chang; Yaoyao Chen; Xiaowei Guo; Xiali Mao; Mingming Wang; Shuai Zhang; Zhou Shi; Yiqi Luo; Lei Cheng; Kailiang Yu; et al. (Global Ecology and Biogeography, 2023)
Aim This study aimed to infer the allocation of belowground net primary productivity (BNPP) to sequential soil depths down to 2 m across the globe at a 1 km resolution and assess underlying environmental drivers. Location Global. Time Period Contemporary (1932–2017). Major Taxa Studied Terrestrial plants. Methods Global datasets including field net primary production (NPP, i.e., the difference between plant assimilated and respired carbon) from 725 soil profiles, root biomass and its depth distribution from 559 soil profiles were compiled and used to infer the depth distribution of BNPP across the globe and digitally map depth‐resolved BNPP globally at 1 km resolution. Drivers of the depth distribution of BNPP were evaluated using machine learning‐based models. Results Global average BNPP allocated to the 0–20 cm soil layer is estimated to be 1.1 Mg C ha −1 yr −1 , accounting for ~60% of total BNPP. Across the globe, the depth distribution of BNPP varies largely, and more BNPP is allocated to deeper layers in hotter and drier regions. Edaphic, climatic and topographic properties (in order of importance) explain >80% of such variability; and the direction and magnitude of the influence of individual properties are soil depth‐ and biome‐dependent. Main Conclusions The findings suggest that mean annual temperature and precipitation are the two most important factors regulating BNPP across the globe. Soil properties such as soil actual evaporation and total nitrogen also play a vital role in regulating the depth distribution of BNPP. The maps of BNPP provide global benchmarks of depth‐resolved BNPP for the prediction of whole‐profile soil carbon dynamics across biomes.

TRPC6 promotes daunorubicin-induced mitochondrial fission and cell death in rat cardiomyocytes with the involvement of ERK1/2-DRP1 activation - Li-Xia Xu; Rui-Xing Wang; Jian-Feng Jiang; Gao-Cheng Yi; Jin-Jin Chang; Rui-Lan He; Hai-Xia Jiao; Bin Zheng; Long-Xin Gui; Jun-Jin Lin; Zhi-Hong Huang; Mo-Jun Lin; et al. (Toxicology and Applied Pharmacology, 2023)

Hypothermic neuroprotection by targeted cold autologous blood transfusion in a non-human primate stroke model - Jian Chen; Shuaili Xu; Hangil Lee; Longfei Wu; Xiaoduo He; Wenbo Zhao; Mo Zhang; Yanhui Ma; Yuchuan Ding; Yongjuan Fu; Chuanjie Wu; Ming Li; et al. (Science Bulletin, 2023)

Petrogenesis and dynamic significance of Miocene-Holocene alkali basalts in the southeastern Tibetan Plateau - Jingkai Wu; Hangshan Lei; Qian Ma; Zhidan Zhao; Fang-Zhen Teng; Shuangquan Zhang; Brian Cousens; Zhuang Miao; Yiyun Yang; Dong Liu; Qing Wang; Di-Cheng Zhu; et al. (Lithos, 2023)

Characterization of modified rice straw biochar in immobilizing Bacillus subtilis 168 and evaluation on its role as a novel agent for zearalenone-removal delivery - Jie Han; Jiao Zhang; Jun Meng; Yuanqi Cai; Mo Cheng; Siyu Wu; Zeming Li (Journal of Hazardous Materials, 2023)

Mineralogy and geochemistry of the Zedong Late Cretaceous (∼94 Ma) biotite granodiorite in the Southern Lhasa Terrane: Implications for the tectonic setting and Cu-Au mineralization - Weice Zhang; Zhidan Zhao; Dong Liu; Kunfeng Qiu; Qing Wang; Di-Cheng Zhu; Tiannan Yang; Yingchao Liu; Rui Wang; Zengqian Hou; Xuanxue Mo (Lithos, 2023)

Rice genotypes and root-associated niches shifted bacterial community in response to pollution of di-(2-ethylhexyl) phthalate (DEHP) for promoting DEHP removal - Cui-Lan Zhu; Hui-Xiong Lü; Yu-Hong Huang; Ji-liang Cheng; Hui Li; Yan-Wen Li; Ce-Hui Mo; Hai-Ming Zhao; Lei Xiang; Quan-Ying Cai (Journal of Hazardous Materials, 2023)

Important effects of polypropylene on migration of ciprofloxacin in groundwater - Yanna Chen; Cehui Mo; Ming Wu; Yanru Hao; Zhou Cheng; Guoping Lu; Qusheng Li; Bill X. Hu; Jianfeng Wu; Jichun Wu (Journal of Environmental Chemical Engineering, 2023)

Deciphering mantle heterogeneity associated with ancient subduction-related metasomatism: Insights from Mg-K isotopes in potassic alkaline rocks - Zhuang Miao; Xiaoqiang Li; Zhidan Zhao; Yaoling Niu; Bo Xu; Hangshan Lei; Jingkai Wu; Yiyun Yang; Qian Ma; Dong Liu; Qing Wang; Di-Cheng Zhu; et al. (Geochimica et Cosmochimica Acta, 2023)

Ultrafast loose nanofiltration membrane intercalated by in-situ grown nanoparticles for dye purification and reuse - Yuting Liu; Jiahao Mo; Huiying Ding; Yanjun Cheng; Zhong Zhang; Chen Wang; Xianhui Li (Desalination, 2023)

Edwardsiella piscicida Ail1: An outer membrane protein required for host infection - Mo-fei Li; Yu-ting Du; Cheng-dong Jin; Xue-peng Li; Yuan-yuan Sun (Aquaculture, 2023)

Flexible three-dimensional covalent organic frameworks for ultra-fast and selective extraction of uranium via hydrophilic engineering - Xiao-Juan Chen; Cheng-Rong Zhang; Xin Liu; Jia-Xin Qi; Wei Jiang; Shun-Mo Yi; Cheng-Peng Niu; Yuan-Jun Cai; Ru-Ping Liang; Jian-Ding Qiu (Journal of Hazardous Materials, 2023)

Modulation of Antioxidant Attributes and Grain Yield in Fragrant Rice by Exogenous Cu Application - Siren Cheng; Zhenming Fang; Xianchao Cheng; Yizhu Wu; Lifang Mo; Chongyang Yan; Langshan Zhou; Yong Ren (Journal of Plant Growth Regulation, 2023)

Microbiological analysis and characterization of Salmonella and ciprofloxacin-resistant Escherichia coli isolates recovered from retail fresh vegetables in Shaanxi Province, China - Chenyang Cao; Wenxing Zhao; Zexun Lü; Yixin Mo; Wei Hu; Shengyuan Sun; Huabin Cheng; Jiaqi Ma; Sirui Xiong; Xiaorong Jin; Hui Yang; Li Bai; et al. (International Journal of Food Microbiology, 2023)

Doxycycline combined manure microbes to enhances biofilm formation of the soil plastisphere and increases the surface bio-risk of microplastics vehicle - Shuo Liu; Wei-Kang Deng; Shi-Hua Niu; Chun-Hao Mo; Xin-Di Liao; Si-Cheng Xing (Chemical Engineering Journal, 2023)

A 2D mesoporous hydrazone covalent organic framework for selective detection and ultrafast recovery of Au(III) from electronic waste - Li Zhang; Jia-Qi Fan; Qiong-Qing Zheng; Sai-Jin Xiao; Cheng-Rong Zhang; Shun-Mo Yi; Xin Liu; Wei Jiang; Quan-Gen Tan; Ru-Ping Liang; Jian-Ding Qiu (Chemical Engineering Journal, 2023)

Impacts of river discharge, coastal geomorphology, and regional sea level rise on tidal dynamics in Pearl River Estuary - Xia Li; Yanzi Cai; Zezheng Liu; Xiaobiao Mo; Li Zhang; Cheng Zhang; Baoshan Cui; Ze Ren (Frontiers in Marine Science, 2023)
Introduction Recently, accelerated sea-level rise (SLR) has raised major concerns on estuarine management and restoration because it modifies estuarine hydrodynamics, such as tidal inundation extent and amplitude, tidal current asymmetry, flood frequency, etc. Understanding underlying processes which regulate estuarine tidal dynamics is critical for mitigating potential impacts on the coastal population and development. Methods We selected the Pearl River Estuary (PRE), an estuary with a higher regional SLR compared to the global SLR as the study area. To identify the effects of regional SLR on tidal dynamics, we analyzed long-term records of four tidal variables from 19 gauge stations between 1952 and 2020, including annual highest tidal levels (AHTLs), annual lowest tidal levels (ALTLs), annual mean tidal ranges (AMTRs), and annual mean tidal levels (AMTLs). Results Results suggested that variability in tidal variables was site-specific. The AMTRs decreased gradually from offshore regions to the upper reaches of rivers with a maximum at the mouth of the estuary. In contrast, the magnitudes of the AHTLs, AMTLs, and ALTLs decreased when approaching the coastline. Distance to the coastline had the highest correlations with the AHTLs, ALTLs, and AMTLs, followed by river width and river depth. The local SLR was responsible for the temporal variability in AHTLs, ALTLs, and AMTLs at the estuarine mouth with correlation coefficients from 0.43 to 0.85 (P < 0.001) but showed low correlations with these three tidal variables at the upper reaches of rivers (P > 0.001). Instead, the tidal variables were highly correlated with river discharge at the upper reaches of rivers, especially for the AHTLs (correlation coefficient = 0.83, P < 0.0001). Conclusions Our study demonstrated that the tidal dynamics demonstrate significant spatial-temporal variability. Geomorphology, river discharge, and sea levels have jointly affected estuarine hydrodynamics.

Revealing microcystin-LR ecotoxicity to earthworm (Eisenia fetida) at the intestinal cell level - Xiang Liu; Jin-Cheng Ye; Fen Li; Rong-Jun Gao; Xiao-Xiao Wang; Ji-Liang Cheng; Bai-Lin Liu; Lei Xiang; Yan-Wen Li; Quan-Ying Cai; Hai-Ming Zhao; Ce-Hui Mo; et al. (Chemosphere, 2023)

Thermodynamic characteristics of methane hydrate formation in high-pressure microcalorimeter under different reaction kinetics - Juan Fu; Jia-Mei Mo; Shi-Jun Liu; Wen-Zhe Yi; Yi-Song Yu; Neng-You Wu; Xiao-Li Chen; Qiu-Cheng Su; Xiao-Sen Li (Fuel, 2023)

Chiral graphene materials for enantiomer separation - Qingsong Cheng; Hebing Pei; Qian Ma; Ruibin Guo; Nijuan Liu; Zunli Mo (Chemical Engineering Journal, 2023)

(4-Picolylamino)-17β-Estradiol derivative and analogues induce apoptosis with death receptor trail R2/DR5 in MCF-7 - Yudong Yin; Li Sun; Lixin Sheng; Liqiong Zhang; Jingjing Liu; Xiaoan Wen; Weibin Mo; Quande Wang; Keguang Cheng (Chemico-Biological Interactions, 2023)

Normal Closure Behavior of Rock Fractures Considering Transition from Elastic Deformation to Fully Plastic Flow - Lin Huang; Cheng Zhao; Bo Li; Yangyang Mo; Jinquan Xing; Huiguan Chen (Rock Mechanics and Rock Engineering, 2023)

Genome-wide identification and expression analysis of the SlNAC gene family in tomato based on a high-quality genome - Xiuling Chen; Fulei Mo; Chunyang Shen; Lingjun Meng; Yuxin Zou; Xiaopeng Xue; Mozhen Cheng; Fanyue Meng; Haonan Qi; Aoxue Wang (Horticulture, Environment, and Biotechnology, 2022)

Gender-specific effects of prenatal mixed exposure to serum phthalates on neurodevelopment of children aged 2–3 years:the Guangxi Birth Cohort Study - Yuan Zheng; Longman Li; Hong Cheng; Shengzhu Huang; Xiuming Feng; Lulu Huang; Luyun Wei; Dehao Cao; Sida Wang; Long Tian; Weijun Tang; Caitong He; et al. (Environmental Science and Pollution Research, 2022)

Association between plasminogen activator inhibitor-1 gene polymorphisms and susceptibility to Parkinson’s disease in Chinese patients - Qi Xu; Qilun Lai; Junjun Wang; Liying Zhuang; Lin Cheng; Yejia Mo; Lu Liu; Zexian Zhao; Ying Zhang; Shiting Weng; Song Qiao (Acta Neurologica Belgica, 2022)

Causal Effect of Genetically Determined Blood Copper Concentrations on Multiple Diseases: A Mendelian Randomization and Phenome-Wide Association Study - Xiuming Feng; Wenjun Yang; Lulu Huang; Hong Cheng; Xiaoting Ge; Gaohui Zan; Yanli Tan; Lili Xiao; Chaoqun Liu; Xing Chen; Zengnan Mo; Longman Li; et al. (Phenomics, 2022)

Neural responses to facial attractiveness in the judgments of moral goodness and moral beauty - Qiuping Cheng; Zhili Han; Shun Liu; Yilong Kong; Xuchu Weng; Lei Mo (Brain Structure and Function, 2022)

Assessment of potential sediment disasters and resilience management of mountain roads using environmental indicators - Chao-Yuan Lin; Yuan-Chung Lai; Shao-Wei Wu; Fan-Chung Mo; Cheng-Yu Lin (Natural Hazards, 2022)
In recent years, extreme rainfall events occur frequently, causing serious watershed sediment disasters, destroying mountain roads, and endangering the safety of residents' lives and property. This study aims to deal with the spatial change of potential sediment movement on the road slope pre-disaster and to screen disaster hot spots for early warning and control system. The conceptual model is used to simulate the distribution of primary and/or derived disasters on a watershed scale to assess the impact of sediment disasters caused by heavy rain event. Correlation analysis shows that the models in assessment of primary disaster and derived disaster are significantly correlated with the collapse ratio and disaster ratio, respectively. Since the primary disaster has been considered when calculating the derived disaster risk, the terrain subdivision along Provincial Highway 21 (Tai-21) is extracted to understand the derived sediment disaster on the road slope. The model can effectively evaluate the road sections prone to disasters. According to the risk level, the hot spot of road slope disasters and the management of disaster resilience are determined and can be the reference for disaster prevention and control.

Lentinan triggers oxidative stress-mediated anti-inflammatory responses in lung cancer cells - Mo Li; Xin Du; Zheng Yuan; Mengzhi Cheng; Penghua Dong; Yu Bai (Molecular and Cellular Biochemistry, 2022)

The combined toxicity and mechanism of multi-walled carbon nanotubes and nano zinc oxide toward the cabbage - Mo Hong; Ji-Lai Gong; Wei-Cheng Cao; Rong Fang; Zhe Cai; Jun Ye; Zeng-Ping Chen; Wang-Wang Tang (Environmental Science and Pollution Research, 2022)

Increased serum levels of cadmium are associated with an elevated risk of cardiovascular disease in adults - Siyu Ma; Jie Zhang; Cheng Xu; Min Da; Yang Xu; Yong Chen; Xuming Mo (Environmental Science and Pollution Research, 2022)

Heavy metals in bamboo shoots from Southeastern China and risk assessment - Mo RunHong; Junyong Cheng; Fubin Tang; JinJun Yue; Zhengxiang Li; Zhanglin Ni (Food Additives & Contaminants Part B-Surveillance, 2021)

Study on synthesis and anticancer activity of 17beta-estradiol-phenol/aniline nitrogen mustard derivatives - Yu-dong Yin; Jing-jing Liu; Wen-fei Liao; Xian-kun Guo; Li-shan Zhang; Wei-bin Mo; Ke-guang Cheng (Medicinal Chemistry Research, 2021)

Microbial carbon-use efficiency and straw-induced priming effect within soil aggregates are regulated by tillage history and balanced nutrient supply - Fei Mo; Ye-Ye Zhang; Yang Liu; Yun-Cheng Liao (Biology and Fertility of Soils, 2021)

Morphological and anatomical characteristics of exserted stigma sterility and the location and function of SlLst (Solanum lycopersicum Long styles) gene in tomato - Mo-zhen Cheng; Chao Gong; Bo Zhang; Wei Qu; Hao-nan Qi; Xiu-ling Chen; Xing-yuan Wang; Yao Zhang; Jia-yin Liu; Xiao-dong Ding; You-wen Qiu; Ao-xue Wang (Theoretical and Applied Genetics, 2021)

An emerging novel bovine coronavirus with a 4-amino-acid insertion in the receptor-binding domain of the hemagglutinin-esterase gene - Keha-mo Abi; Qi Zhang; Bin Zhang; Long Zhou; Hua Yue; Cheng Tang (Archives of Virology, 2020)

Whether the carbon emission from green roofs can be effectively mitigated by recycling waste building material as green roof substrate during five-year operation? - Liangqian Fan; Jingting Wang; Xiaoling Liu; Hongbing Luo; Ke Zhang; Xiaoying Fu; Mei Li; Xiaoting Li; Bing Jiang; Jia Chen; Shuzhi Fu; You Mo; et al. (Environmental Science and Pollution Research, 2020)

Genomic analyses of heat stress transcription factors (HSFs) in simulated drought stress response and storage root deterioration after harvest in cassava - Jian Zeng; Chunlai Wu; Cheng Wang; Fengfeng Liao; Jiajia Mo; Zehong Ding; Weiwei Tie; Yan Yan; Wei Hu (Molecular Biology Reports, 2020)

The effect of follower load on the range of motion, facet joint force, and intradiscal pressure of the cervical spine: a finite element study - Xin-Yi Cai; Chen-Xi YuChi; Cheng-Fei Du; Zhong-Jun Mo (Medical & Biological Engineering & Computing, 2020)

Genetic analysis and fine mapping of the gall midge resistance gene Gm5 in rice (Oryza sativa L.) - Hailian Zhou; Xinyi Wang; Yi Mo; Yang Li; Liuhui Yan; Zhihua Li; Wan Shu; Ling Cheng; Fengkuan Huang; Yongfu Qiu (Theoretical and Applied Genetics, 2020)

Characterization and application of a gall midge resistance gene (Gm6) from Oryza sativa ‘Kangwenqingzhan’ - Yang Li; Yi Mo; Zhihua Li; Meng Yang; Lihua Tang; Ling Cheng; Yongfu Qiu (Theoretical and Applied Genetics, 2020)

Correction to: Associations of trace elements in blood with the risk of isolated ventricular septum defects and abnormal cardiac structure in children - Yu Zhu; Cheng Xu; Yuxi Zhang; Zongyun Xie; Yaqin Shu; Changgui Lu; Xuming Mo (Environmental Science and Pollution Research, 2020)

MicroRNA-365 Knockdown Prevents Ischemic Neuronal Injury by Activating Oxidation Resistance 1-Mediated Antioxidant Signals - Jia-Lin Mo; Zhi-Guang Pan; Xiao Chen; Yu Lei; Ling-Ling Lv; Cheng Qian; Feng-Yan Sun (Neuroscience Bulletin, 2019)

The clinical and prognostic significance of paraoxonase-2 in gastric cancer patients: immunohistochemical analysis - Xiaohua Wang; Guifang Xu; Jingyuan Zhang; Shuaiyu Wang; Min Ji; Lei Mo; Mengxia Zhu; Jun Li; Guoren Zhou; Jianwei Lu; Cheng Chen (Human Cell, 2019)

Associations between mercury exposure and the risk of nonalcoholic fatty liver disease (NAFLD) in US adolescents - Runsen Chen; Yang Xu; Cheng Xu; Yaqin Shu; Siyu Ma; Changgui Lu; Xuming Mo (Environmental Science and Pollution Research, 2019)

Occurrence of Bryde's whales, Balaenoptera edeni , in the northern Beibu Gulf, China - Mo Chen; Shiang‐Lin Huang; Haiping Wu; Zhigang Mei; Yiwen Chen; Jingsong Zheng; Wen Cheng; Keshun Deng; Chengteng Yang; Mao Chen; Chun‐Chieh Wang; Derun Lin; et al. (Marine Mammal Science, 2019)

Associations of trace elements in blood with the risk of isolated ventricular septum defects and abnormal cardiac structure in children - Yu Zhu; Cheng Xu; Yuxi Zhang; Zongyun Xie; Yaqin Shu; Changgui Lu; Xuming Mo (Environmental Science and Pollution Research, 2019)

Geochemical and isotopic (U, Th) variations in lake waters in the Qinghai Lake Basin, Northeast Qinghai-Tibet Plateau, China: origin and paleoenvironmental implications - Pu Zhang; Hai Cheng; Weiguo Liu; Lingtong Mo; Xiangzhong Li; Youfeng Ning; Ming Ji; Baoyun Zong; Chen Zhao (Arabian Journal of Geosciences, 2019)

Surface mulching and a sandy soil interlayer suppress upward enrichment of salt ions in salt-contaminated field - Jianyong Wang; Huiming Liu; Shaoming Wang; Yingxia Liu; Zhengguo Cheng; Guangqiang Fu; Fei Mo; Youcai Xiong (Journal of Soils and Sediments, 2019)

Direct and legacy effects of herbivory on growth and physiology of a clonal plant - Bi-Cheng Dong; Mo-Zhu Wang; Rui-Hua Liu; Fang-Li Luo; Hong-Li Li; Fei-Hai Yu (Biological Invasions, 2018)

Ultrasonic seed treatment improved physiological and yield traits of rice under lead toxicity - Gangshun Rao; Umair Ashraf; Suihua Huang; Siren Cheng; Muhammad Abrar; Zhaowen Mo; Shenggang Pan; Xiangru Tang (Environmental Science and Pollution Research, 2018)

Molecular characterization of two novel sub-sublineages of pigeon paramyxovirus type 1 in China - Tianchao Wei; Qiaomu Deng; Haiqiong Li; Chao Pan; Guosheng Zhai; Yadong Yuan; Ercai Cheng; Yuanqin Zhang; Meilan Mo; Teng Huang; Ping Wei (Archives of Virology, 2018)

Synergetic effect of hydrochar on the transport of anatase titanium dioxide nanoparticles in the presence of phosphate in saturated quartz sand - Xueying Cheng; Nan Xu; Xinxing Huangfu; Xing Zhou; Mo Zhang (Environmental Science and Pollution Research, 2018)

Multifractal Detrended Fluctuation Analysis of Regional Precipitation Sequences Based on the CEEMDAN-WPT - Dong Liu; Chen Cheng; Qiang Fu; Chunlei Liu; Mo Li; Muhammad Abrar Faiz; Tianxiao Li; Muhammad Imran Khan; Song Cui (Pure and Applied Geophysics, 2018)

Effect of nicotine from tobacco root exudates on chemotaxis, growth, biocontrol efficiency, and colonization by Pseudomonas aeruginosa NXHG29 - Li Ma; Shuai Chao Zheng; Ti Kun Zhang; Zi Yi Liu; Xue Jian Wang; Xing Kui Zhou; Cheng Gang Yang; Jin Ling Duo; Ming He Mo (Antonie van Leeuwenhoek, 2018)

The association between serum copper concentrations and cardiovascular disease risk factors in children and adolescents in NHANES - Xiaodong Zang; Hesuyuan Huang; Zhulun Zhuang; Runsen Chen; Zongyun Xie; Cheng Xu; Xuming Mo (Environmental Science and Pollution Research, 2018)

Postnatal Subacute Benzo(a)Pyrene Exposure Caused Neurobehavioral Impairment and Metabolomic Changes of Cerebellum in the Early Adulthood Period of Sprague-Dawley Rats - Chunlin Li; Jing Wang; Qiuping Su; Kai Yang; Chengzhi Chen; XueJun Jiang; Tingli Han; Shuqun Cheng; Tingting Mo; Ruiyuan Zhang; Bin Peng; Yuming Guo; et al. (Neurotoxicity Research, 2018)

GbABR1 is associated with Verticillium wilt resistance in cotton - Yujia Liu; Xin Liu; Lu Long; Weina Wang; Quan Sun; Bo Li; Chenxiao Wang; Jieru Cheng; Yuanyuan Zhang; Yuanhui Xie; Lingling Xu; Runkuan Qin; et al. (Biologia, 2018)

Associations between total mercury and methyl mercury exposure and cardiovascular risk factors in US adolescents - Yuxi Zhang; Cheng Xu; Zhi Fu; Yaqin Shu; Jie Zhang; Changgui Lu; Xuming Mo (Environmental Science and Pollution Research, 2018)

Bacillus zanthoxyli sp. nov., a novel nematicidal bacterium isolated from Chinese red pepper (Zanthoxylum bungeanum Maxim) leaves in China - Ma Li; Cao Yong Hong; Wang Xiao Yan; Zheng Shuai Chao; Yang Cheng Gang; Duo Jin Ling; Zhou Xing Kui; Xi Jia Qin; Zhu Ming Liang; Mo Ming He (Antonie van Leeuwenhoek, 2017)

ApoA-I/SR-BI modulates S1P/S1PR2-mediated inflammation through the PI3K/Akt signaling pathway in HUVECs - Kun Ren; Yan-Ju Lu; Zhong-Cheng Mo; Xing -Liu; Zhen-Li Tang; Yue Jiang; Xiao-Shan Peng; Li Li; Qing-Hai Zhang; Guang-Hui Yi (Journal of Physiology and Biochemistry, 2017)

Molecular characterisation and functional analysis of a cytochrome P450 gene in cotton - Kexue Zhou; Lu Long; Quan Sun; Weina Wang; Wei Gao; Zongyan Chu; Chaowei Cai; Jianchuan Mo; Jieru Cheng; Xiangrui Zhang; Yujia Liu; Xiongming Du; et al. (Biologia, 2017)

ApoA-I induces S1P release from endothelial cells through ABCA1 and SR-BI in a positive feedback manner - Xing Liu; Kun Ren; Rong Suo; Sheng-Lin Xiong; Qing-Hai Zhang; Zhong-Cheng Mo; Zhen-Li Tang; Yue Jiang; Xiao-Shan Peng; Guang-Hui Yi (Journal of Physiology and Biochemistry, 2016)

PA-X-associated early alleviation of the acute lung injury contributes to the attenuation of a highly pathogenic H5N1 avian influenza virus in mice - Jiao Hu; Yiqun Mo; Zhao Gao; Xiaoquan Wang; Min Gu; Yanyan Liang; Xin Cheng; Shunlin Hu; Wenbo Liu; Huimou Liu; Sujuan Chen; Xiaowen Liu; et al. (Medical Microbiology and Immunology, 2016)

G2 rotavirus within an emergent VP7 evolutionary lineage circulating in children with acute diarrhea in Guangxi Province of China, 2014 - Hui Jin Dong; Yuan Qian; You Zhang; Lin Qing Zhao; Ru Nan Zhu; Yi Nong; Zhao Jun Mo; Rong Cheng Li (Archives of Virology, 2016)

Food wastes as fish feeds for polyculture of low-trophic-level fish: bioaccumulation and health risk assessments of heavy metals in the cultured fish - Zhang Cheng; Cheung-Lung Lam; Wing-Yin Mo; Xiang-Ping Nie; Wai-Ming Choi; Yu-Bon Man; Ming-Hung Wong (Environmental Science and Pollution Research, 2016)

The use of food waste-based diets and Napier grass to culture grass carp: growth performance and contaminants contained in cultured fish - Zhang Cheng; Wing-Yin Mo; Xiang-Ping Nie; Kai-Bing Li; Wai-Ming Choi; Yu-Bon Man; Ming-Hung Wong (Environmental Science and Pollution Research, 2016)

Use of food waste as fish feeds: effects of prebiotic fibers (inulin and mannanoligosaccharide) on growth and non-specific immunity of grass carp (Ctenopharyngodon idella) - Wing Y. Mo; Zhang Cheng; Wai M. Choi; Clare H. I. Lun; Yu B. Man; James T. F. Wong; Xun W. Chen; Stanley C. K. Lau; Ming H. Wong (Environmental Science and Pollution Research, 2015)

Evolution process of the Late Silurian–Late Devonian tectonic environment in Qimantagh in the western portion of east Kunlun, China: Evidence from the geochronology and geochemistry of granitoids - NANA HAO; WANMING YUAN; AIKUI ZHANG; YUNLEI FENG; JIANHUI CAO; XIAONING CHEN; XUEQIN CHENG; XUANXUE MO (Journal of Earth System Science, 2015)

Environmental mercury concentrations in cultured low-trophic-level fish using food waste-based diets - Zhang Cheng; Wing Yin Mo; Yu Bon Man; Cheung Lung Lam; Wai Ming Choi; Xiang Ping Nie; Yi Hui Liu; Ming Hung Wong (Environmental Science and Pollution Research, 2015)

Parallel simulation of groundwater flow in the North China Plain - Tangpei Cheng; Jingli Shao; Yali Cui; Zeyao Mo; Zhong Han; Ling Li (Journal of Earth Science, 2014)

Gadolinium promoted proliferation in mouse embryo fibroblast NIH3T3 cells through Rac and PI3K/Akt signaling pathways - Liming Shen; Aochu Yang; Pengwei Yao; Xiaohong Sun; Cheng Chen; Cuiping Mo; Lei Shi; Youjiao Chen; Qiong Liu (BioMetals, 2014)

Effect of miR-205 on 3T3-L1 preadipocyte differentiation through targeting to glycogen synthase kinase 3 beta - Jingwei Yu; Yaosheng Chen; Limei Qin; Luxi Cheng; Guangcai Ren; Peiqing Cong; Delin Mo; Zuyong He (Biotechnology Letters, 2014)

Efficacy of Various Combined Blood Purification Techniques for Treating Patients with Non-viral Acute Liver Failure - Mao-qin Li; Jia-qiong Li; Zai-xiang Shi; Ji-yuan Xu; Zhou Zhang; Fei Lu; Lin Li; Yan-jun Xu; Xun Mo; Bo Lu; Xiao-meng Wang; Li-li Ma; et al. (Cell Biochemistry and Biophysics, 2014)

Continuous evolution of avian infectious bronchitis virus resulting in different variants co-circulating in southern China - Meng Li; Mei-Lan Mo; Bai-Cheng Huang; Wen-Sheng Fan; Zheng-Ji Wei; Tian-Chao Wei; Kang-Ran Li; Ping Wei (Archives of Virology, 2013)

Phylogenetic diversity of bacterial endophytes of Panax notoginseng with antagonistic characteristics towards pathogens of root-rot disease complex - Li Ma; Yong Hong Cao; Ming Hui Cheng; Ying Huang; Ming He Mo; Yong Wang; Jian Zhong Yang; Fa Xiang Yang (Antonie van Leeuwenhoek, 2013)

Mechano growth factor (MGF) promotes proliferation and inhibits differentiation of porcine satellite cells (PSCs) by down-regulation of key myogenic transcriptional factors - Li-Li Qin; Xiao-Kui Li; Jian Xu; De-Lin Mo; Xiong Tong; Zhi-Cheng Pan; Jia-Qi Li; Yao-Sheng Chen; Zhe Zhang; Chong Wang; Qiao-Ming Long (Molecular and Cellular Biochemistry, 2012)

Effect of C/N ratios on the performance of earthworm eco-filter for treatment of synthetics domestic sewage - Yong-Jun Zhao; Cheng Yan; Yin-Liang Li; Ji-Hua Li; Mo Yang; Er Nie; Zheng Zheng; Xing-Zhang Luo (Environmental Science and Pollution Research, 2012)

Unloading the infarcted heart affect MMPs–TIMPs axis in a rat cardiac heterotopic transplantation model - Wei-jian Wang; Zi-li Meng; Yun-chang Mo; Jun-wei Liu; Cheng-chao Sun; Sheng-shou Hu; Hao Zhang (Molecular Biology Reports, 2012)

Analysis of genetic variations in the dopamine D1 receptor (DRD1) gene and antipsychotics-induced tardive dyskinesia in schizophrenia - I-Ching Lai; Geng-Han Mo; Mao-Liang Chen; Ying-Chieh Wang; Jen-Yeu Chen; Ding-Lieh Liao; Ya-Mei Bai; Chao-Cheng Lin; Tzu-Ting Chen; Ying-Jay Liou (European Journal of Clinical Pharmacology, 2011)

Rapid simultaneous screening of seven clinically important enteric pathogens using a magnetic bead based DNA microarray - Hong Sun; Qiu-Hua Mo; Ji-Can Lin; Ze Yang; Cheng-Ning Tu; Da-Yong Gu; Lei Shi; Wei-Ping Lu (World Journal of Microbiology and Biotechnology, 2011)

A formation pressure prediction method based on tectonic overpressure - Bo Shen; Chao-Mo Zhang; Zhi-Qiang Mao; Cheng-Wen Xiao (Applied Geophysics, 2010)

Transmutation of ancient settlements and environmental changes between 6000–2000 aBP in the Chaohu Lake Basin, East China - Li Wu; Xinyuan Wang; Kunshu Zhou; Duowen Mo; Cheng Zhu; Chao Gao; Guangsheng Zhang; Lan Li; Li Liu; Weiguang Han (Journal of Geographical Sciences, 2010)

13C abundance, water-soluble and microbial biomass carbon as potential indicators of soil organic carbon dynamics in subtropical forests at different successional stages and subject to different nitrogen loads - Hua-Jun Fang; Gui-Rui Yu; Shu-Lan Cheng; Jiang-Ming Mo; Jun-Hua Yan; Shenggong Li (Plant and Soil, 2009)

Identification of Cellulase Genes from the Metagenomes of Compost Soils and Functional Characterization of One Novel Endoglucanase - Hao Pang; Peng Zhang; Cheng-Jie Duan; Xin-Chun Mo; Ji-Liang Tang; Jia-Xun Feng (Current Microbiology, 2009)

Src homology 2-containing phosphotyrosine phosphatase regulates endothelin-1-induced epidermal growth factor receptor transactivation in rat renal tubular cell NRK-52E - Chen Cheng-Hsien; Hsu Yung-Ho; Sue Yuh-Mou; Hou Chun-Cheng; Lee Horng-Mo; Huang Huei-Mei; Chen Tso-Hsiao (Pflügers Archiv - European Journal of Physiology, 2006)

Seasonal variations of riverine organic carbon contents in Makou and Hekou gauge stations of the Zhujiang River, China - Quan-zhou Gao; Cheng-de Shen; Yan-min Sun; Wei-xi Yi; Jia-mo Fu; Guo-ying Sheng (Chinese Geographical Science, 2000)